Pengembangan Media Pembelajaran Digital Berbasis Google Sites dengan Model ADDIE Pada Materi Pendidikan Pancasila di Sekolah Dasar - Siti Dhinda Tiarani; Yalvema Miaz; Muhammadi Muhammadi; Ulfia Rahmi (Jurnal Inovasi Pendidikan dan Pembelajaran Sekolah Dasar, 2025)
This study developed a Google Sites–based digital learning medium to enhance Civic Education learning for grade V elementary school students. Preliminary analysis revealed that learning was still dominated by teacher-centred methods, limited media use, and low student engagement, indicating the need for interactive digital resources. The study aimed to produce a valid, practical, and effective learning medium for the topic “Norma dalam Kehidupanku.” Using the ADDIE development model, the research followed a systematic procedure comprising needs analysis, media design, digital content development, expert validation, limited implementation, revision, and final evaluation. Participants included grade V teachers and students from three public elementary schools in Padang. Data were collected through expert validation sheets, practicality questionnaires, and pretest–posttest assessments, and analyzed using percentage scores and N-Gain. Results showed very high validity (93.89%), teacher practicality (99.17%), and student practicality (87.82%). Effectiveness testing demonstrated significant improvement in learning outcomes, with the average score increasing from 78.9 (pretest) to 96.6 (posttest) and an N-Gain of 0.90 (high category). These findings confirm that Google Sites–based media effectively support interactive, accessible, and contextual Civic Education learning in elementary schools.